2021
DOI: 10.3390/jcm10061154
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of the Responses to Treatment of Mycoplasma pneumoniae Pneumonia

Abstract: The prevalence of refractory Mycoplasma pneumoniae (MP) pneumonia is increasing. The present study aimed to identify the predictive factors of responses to treatment of MP pneumonia in children. A total of 149 children were diagnosed with MP pneumonia, of whom 56 were included in the good response group, 75 children in the slow response group, and 18 children in no response or progression group. Data on the clinical, laboratory, and radiologic features were retrospectively obtained through medical chart review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…An increased LDH level can reflect the degree of tissue damage and lysis. Lee et al ( 15 ) found that the CRP and LDH levels can be used to reflect the therapeutic effect of MPP in children. Wang et al ( 16 ) showed that age, the total heat course, and the CRP, LDH and ESR levels in children with MPP mucus plug blockage were higher than those in the healthy subject group, suggesting that the increase in CRP, LDH and ESR can be used as an indicator of airway mucus embolism in children with MPP.…”
Section: Discussionmentioning
confidence: 99%
“…An increased LDH level can reflect the degree of tissue damage and lysis. Lee et al ( 15 ) found that the CRP and LDH levels can be used to reflect the therapeutic effect of MPP in children. Wang et al ( 16 ) showed that age, the total heat course, and the CRP, LDH and ESR levels in children with MPP mucus plug blockage were higher than those in the healthy subject group, suggesting that the increase in CRP, LDH and ESR can be used as an indicator of airway mucus embolism in children with MPP.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies reported predictive factors for a poor response to treatment in cases of MP pneumonia such as LDH, interleukin 18, and ferritin levels [ 15 , 23 , 24 ], to date, no study has focused on the clinical significance of pleural effusion in MP pneumonia. A previous study investigated the characteristics of pleural effusion in MP pneumonia in children and proved the presence of MP in the pleural effusion using PCR [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…MP pneumonia was defined using the following three criteria: (1) acute respiratory symptoms, including fever, cough, and/or sputum; (2) proven MP infection based on the results of MP-specific IgM using blood samples and polymerase chain reaction (PCR) analysis of the sputum samples; and (3) abnormal chest radiograph and/or abnormal findings on physical examination, including abnormal breathing sounds. The presence of pleural effusion was diagnosed based on chest radiography findings [ 14 , 15 ]. The local Institutional Review Board (IRB) approved this study and waived the need for informed consent because of the retrospective study design (IRB No.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations